If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56ty + -11 = 247 Reorder the terms: -11 + 56ty = 247 Solving -11 + 56ty = 247 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 56ty = 247 + 11 Combine like terms: -11 + 11 = 0 0 + 56ty = 247 + 11 56ty = 247 + 11 Combine like terms: 247 + 11 = 258 56ty = 258 Divide each side by '56y'. t = 4.607142857y-1 Simplifying t = 4.607142857y-1
| 200-3y-4x=0 | | 8.1-0.6t=7.2 | | 7(2x+10)=6x+26+6x+4 | | a-95=25 | | gcf=42x+28y | | b-5+0.2b=-0.2 | | -8(7)+y=4 | | x^5-3x^4-x^3+3x^2=f(x) | | 2/3+3x+1/4=5/3 | | -8(3)+y=4 | | 3.2x-0.88+1.2=0 | | -8(-2)+y=4 | | 2(5x+4)+2=60 | | 4g-8=-20 | | X*2+5x+3=0 | | 2+3(5+5v)=62 | | 42x+28y=gcf | | -2(3y-4)-y=-4(y-2) | | 3(3x+2)=6(2x-3) | | 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) | | 5y+35=x+5 | | G(10)=50 | | 7x-47=x | | G(7)=98 | | 8x+23=3x+128 | | 20(-2+x)+10=50(-1+4x) | | 8x-10=7x-5 | | F(4)=96 |